Apocalyptic Visions - Hussain, Amir (The journal of religion and film, 2000)
On November 20, 1999, I was privileged to chair a session of the Religion, Film and Visual Culture group at the annual meeting of the American Academy of Religion (AAR). The session was entitled "Film and the Apocalypse", and consisted of the five papers that are collected in this volume. The word "apocalypse" comes from a Greek root meaning to reveal or uncover, which is precisely what I understand films to do, reveal something about the world. In these five papers, much is revealed about the apocalyptic visions of a number of contemporary Hollywood films. This essay will be a summary of and reflection on those five papers.